Transient Stability Enhancement of Power System Using TCSC - Pasuparti Sunil Kumar (Institute of Advanced Engineering and Science, 2012)
This project presents the variable effective fundamental equivalent reactance capability of TCSC for enhancing the transient stability of power systems. For obtaining the varying effective fundamental equivalent reactance, two different controllers namely a speed deviation based Self-tuning Fuzzy PID Controller and a nonlinear controller are used. To validate the performance of the control schemes, the simulation studies are carried out on a single machine infinite bus system using MATLAB/ SIMULINK software package. The results of computer simulation indicate that Self-tuning Fuzzy PID controlled TCSC can not only improve the static stability of system, but also effectively damp power oscillation and enhance the transient stability of system when the power system suffers small disturbance and short circuit. In addition, it also illuminates that Self-tuning Fuzzy PID Controlled TCSC is more effective than nonlinear control, traditional PID control and fixed series compensation.DOI:http://dx.doi.org/10.11591/ijece.v2i3.245